Soft Computing Methodology for Shelf Life Prediction of Processed Cheese - Sumit Goyal; Gyanendra Kumar Goyal (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
Feedforward multilayer models were developed for predicting shelf life of processed cheese stored at 30o C. Input variables were Soluble nitrogen, pH, Standard plate count, Yeast & mould count and Spore count. Sensory score was taken as output parameter for developing feedforward multilayer models. Mean square error, root mean square error, coefficient of determination and nash - sutcliffo coefficient performance measures were implemented for testing prediction potential of the soft computing models. The study revealed that soft computing multilayer models can predict shelf life of processed cheese.DOI: http://dx.doi.org/10.11591/ij-ict.v1i1.506